An Analysis of Negative Politeness Strategies in an English Textbook - Hutagalung, Riris Theresia; Mutiara, Rika (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to investigate how negative politeness strategies are represented in language use, particularly through dialogue in educational resources, such as English textbooks for junior high school students. This study uses a descriptive qualitative approach with content analysis to analyze and describe the collected data. The researchers adapted the politeness theoretical framework developed by Brown and Levinson (1987), focusing on the representation of negative politeness that emerged in the English textbook entitled “An Analysis of Negative Politeness Strategies in an English Textbook” published by the Ministry of Education, Culture, Research, and Technology. The findings indicate that there are five sub-strategies realized in the textbook. They are question and hedge, be conventionally indirect, give deference, minimize the imposition, and be pessimistic. The dominant sub-strategy found was conventionally indirect. A strategy of negative politeness in which the speaker conveys a request or intention indirectly, usually through expressions that contain meanings beyond their literal meaning. This strategy aims to mitigate the potential for face-threatening actions, such as requests or orders, by employing socially acceptable forms of polite expression. Keywords: English for Nusantara Textbook, Politeness strategies, Negative Politeness Strategies